Can lifestyle interventions improve Canadian men's mental health? Outcomes from the HAT TRICK programme. (27th November 2020) - Sharp, Paul; Stolp, Sean; Bottorff, Joan L; Oliffe, John L; Hunt, Kate; Caperchione, Cristina M
Summary: Engaging men in mental health promotion can be difficult because of reticence about help-seeking, especially for gender neutral programmes. Developments in men's health research has pointed to the success of gender-sensitized programmes to increase men's engagement in healthy lifestyle interventions targeting physical activity and healthy eating; however, less is known about the impact of these interventions on men's mental health. This study explored changes to men's depression risk and health-related quality of life at post-intervention (12 weeks) and 9-month follow-up, after participating in HAT TRICK, a gender-sensitized lifestyle intervention for overweight men. Participants completed validated self-report measures of mental health at baseline, post-intervention (12 weeks) and 9-month follow-up. Men's scores on the Male Depression Risk Scale (MDRS) and the SF-12 questionnaire, including physical health (PH12) and mental health (MH12) composite scores, were analyzed using mixed linear models to assess linear trends. At baseline, men ( N  = 62) had a mean age of 50.98 (SD = 10.09) years and BMI of 35.87 (SD = 5.51) kg/m 2 . Results show that both the MDRS and the MH12 showed improvements in participants' mental health, with significant linear trends ( p = 0.003; p = 0.003) qualified with significant quadratic trends over time ( p = 0.02; p = 0.03). There were no significant changes in the PH12 over time. Gender-sensitized programmes for overweight men, such as HAT TRICK, are a promising approach to positively influence components of men's mental health, with the potential for sustained improvements over the long term.